For PhD-Holding Registered Nurses Employed in Clinical Settings, Nursing Management Is Important - Faleh Ali Abdullah Alsaloli; Fatimah Faiz Abdullah Alsaloli; Nora Mubark Masoud Al-Shahrani; Ghaliah Saleh Ayed Alshamrani; Fajer Saud Alklobi; Nourah Saleh Ayed Alshamrani; Fatimah Haib Albuhmod; Ahmed Mohammed Aleissa; Fatimah Ali Aldakhlan; Yahya Ali Saleh Ghazwani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Registered nurses (RNs) with a PhD have the potential to enhance evidence-based nursing (EBN) and improve patient outcomes through their advanced expertise. However, their contributions in clinical practice settings are often underexplored and underutilized. Understanding their roles, challenges, and experiences is critical to leveraging their competencies for advancing nursing care quality and safety. Methods: This study employed semi-structured interviews with 13 PhD-prepared RNs working in clinical practice. Data were collected through audio-recorded interviews, transcribed verbatim, and analyzed using inductive content analysis. Themes were developed collaboratively by the research team to encapsulate participants’ experiences. Results: The analysis revealed four main categories: (1) striving to develop nursing care with or without adequate support, (2) engaging intentionally in clinical practice, (3) promoting evidence-based nursing, and (4) fostering nursing education and professional growth. Participants highlighted their desire to integrate research into clinical practice, mentor colleagues, and improve patient care through EBN. However, barriers such as insufficient managerial support, unclear role definitions, and resistance from peers limited their potential contributions. A comprehensive theme, "Striving for Excellence in Nursing amidst Challenges," encapsulated the findings, reflecting participants’ dedication despite facing obstacles. Conclusion: PhD-prepared RNs bring valuable expertise to clinical practice, enhancing care quality and professional growth. However, their contributions are often hindered by systemic challenges. Addressing these barriers through clear role definitions, managerial support, and fostering a culture of EBN can maximize the impact of RNs with a PhD on patient outcomes and nursing practice.